Catalogue of late and ptolemaic period anthropoid sarcophagi in the Grand Egyptian Museum - Leitz, Christian (Egyptologist), (Grand Egyptian Museum - Catalogue général ;, 2018)
Excavations (Archaeology); Egypt.